RAIN IRREGULARITIES IN THE CENTRAL WEST REGION AND HOW THIS AFFECTS SPRINGS AND WATER RESERVOIRS IN THE FEDERAL DISTRICT - dos Santos Lemos, Adna; de Araújo Prediger, Renata (Journal of Interdisciplinary Debates, 2023)
Meteorological phenomena are consequences of climate change that can be observed during the historical series to identify trends or changes in time series as water and energy transfer on the Earth’s surface and lower atmosphere. The objective of this article was to analyze the rainfall irregularities in the Midwest region and how this affects the springs of the Federal District, resulting in a considerable decrease in the state’s reservoirs, being seen as a determining factor, the La Niña phenomenon, responsible for rainfall irregularities in the Midwest.